Fabrication of a tunable photothermal actuator via in situ oxidative polymerization of polydopamine nanoparticles in hydrogel bilayers - Lee, Chaewon; Park, Jin Hyeok; Kim, Mina; Kim, Jong Sik; Shim, Tae Soup (Soft Matter, 2022)
Photothermally triggered actuation enables the remote and local control of a material. The complex actuation can be achieved by controlling the photothermal efficiency of the material, which is crucial for the development of soft actuators. In this study, the photothermal efficiency of a hydrogel bilayer actuator consisting of a passive agarose/alginate double-network hydrogel layer and an active poly(N-isopropylacrylamide) (PNIPAm) layer was controlled via in situ oxidative polymerization of polydopamine nanoparticles (PDA NPs). Highly concentrated PDA NPs were successfully incorporated into the hydrogel bilayer without interrupting or weakening the polymer network during polymerization. The photothermal efficiency of the actuator was controlled using the number of polymerization cycles. Upon light irradiation, the heat generated by the photothermal effect of PDA NPs caused the shrinkage of the PNIPAm layer, resulting in the shape-morphing of the bilayer. The broad light absorption properties of PDA NPs allowed the bilayer to actuate under sunlight or visible light. Finally, we demonstrated controlled photothermal actuation using a pinwheel-shaped actuator consisting of four panels with different photothermal efficiencies.
Keywords: Bi-layer; Bilayer actuators; Local control; Photo-thermal; Photothermally; Poly(N-isopropylacrylamide); Polydopamine; Situ oxidative polymerization; Soft actuators; Tunables